Effect of sonication and clay content on the properties of unsaturated polyester/montmorillonite nanocomposites. (January 2017) - Romanzini, Daiane; Silva, Adriana A; Soares, Bluma G; Zattera, Ademir J; Amico, Sandro C
The aim of this work is to evaluate the effect of sonication and clay content on the crosslinking and curing characteristics and the final properties of unsaturated polyester/montmorillonite nanocomposites. The Cloisite 30B clay (1, 3 or 5 wt.%) was dispersed in the resin by mechanical stirring and sonication at different ultrasonic amplitudes (20% and 30%). Amplitude is one of the most important parameter when reproducing sonication results. An increase in viscosity with clay incorporation, at 20% amplitude, was related to the better dispersion, corroborating differential scanning calorimetry results. The sequential diffractograms confirmed the influence of the clay on resin crosslinking and the curing process. An intercalated structure was observed for samples up to 3 wt.% of clay and an amplitude of 20% during sonication, corroborating the increase in flexural strength and lower values of coefficient of thermal expansion. Modulus increased with the incorporation of clay, whereas impact strength and linear burning rate declined.